ĐẶC ĐIỂM TIÊU HÌNH CỦA CORINDON ĐĂK TÔN - Thuyết, Nguyễn Thị Minh; Nhung, Ngụy Tuyết; Khôi, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2011)
The typomorphic characteristics of corundum in Dak Ton, Dak Nong Dak Ton is the highest potential mining area of corundum from Dak Nong province. The results of XRD, EPMA, LA-ICPMS and gemology have established the typomorphic characteristics of corundum from this mine. The corundums from Dak Nong are characterized by: sapphire, fancy sapphire varieties, almost stones are dark blue, fewer are blue, green and yellow - BGY group. The color zoning is straight; and have low contents in Cr (<10ppm), Mg (4.61-32.58ppm), high contents in Fe (1141.3-14297.49ppm), Ti (19.99-541ppm), Ga (100ppm-205.53ppm), V (6.6-37.25ppm); (5) typically inclusions: ilmenite, plagioclase, pyrochlore and columbite.